Outpatient monthly plasmapheresis with post-PLEX evinacumab in pediatric homozygous familial hypercholesterolemia: a case report on port access and immunoglobulin preservation - Filler, Guido; Norozi, Kambiz (Frontiers in Pediatrics, 2025)
Homozygous familial hypercholesterolemia (HoFH) is a rare genetic disorder characterized by severely elevated low-density lipoprotein (LDL) cholesterol levels, predisposing patients to early cardiovascular disease. While LDL apheresis is the standard extracorporeal therapy, plasmapheresis (PLEX) is often used in younger children due to limitations in vascular access. Evinacumab, an ANGPTL3 inhibitor, has emerged as an effective adjunct for lowering LDL cholesterol. This case, to our knowledge, describes the first pediatric outpatient implementation of monthly plasmapheresis with post-PLEX Evinacumab infusions, enabled by dual-port access and Octaplasma support to maintain immunoglobulin levels. This report highlights procedural innovations that enabled sustained therapy and emphasizes the need for standardized approaches for combining Evinacumab with extracorporeal treatment in pediatric HoFH.